The image of an employee in Russian psychological studies: a desk study - Shilova, Tamara (2021)
The article covers the background of Russian psychological studies on the image of an employee. The article deals with the self-concept as a building block of the image of an employee. The author analyzes the role of professional self-determination, motivational characteristics and mental regulators in creating the image of an employee.